An Incremental Relaying Approach for Superposition Modulated Cooperative Transmission - Hasan, Cengis; Aygölü, Ümit (IEEE, 2009)
This paper presents a novel cooperative transmission scheme based on superposition modulation and incremental relaying. Incremental relaying is provided by a hybrid automatic-repeat-request (ARQ) type feedback channel. In the proposed scheme, users utilize decode-and-forward method with superposition modulation in which each user superimposes partner's signal if the destination has sent a negative acknowledgement (NACK) in the previous slot. In other words, relaying is performed under the control of feedback data. In case of an acknowledgment (ACK) from the destination, the users transmit merely their own signal. It is shown that at low signal-to-noise ratio (SNR) values the proposed scheme has a better diversity gain than the classical superposition modulated cooperative transmission and is about 1.5-2 dB better in error performance than the existing superposition based decode-and-forward cooperative scheme which means that incremental relaying brings significant gain in SNR.